Associação de cromossomopatias humanas com uso e ocupação do solo em regiões brasileiras: estudo retrospectivo de 2005 a 2015 - Cochak, Marcos Roberto (2017)
population, responsible for spontaneous abortions, problems related to infertility, and a large number of congenital anomalies that cause psychosocial and economic impact in families and also in the health system. They are present in about 1% of the liveborn, 2% of the conceptions known in women over the age of 35 years and almost all the abortions occurred in the first trimester of gestation. These anomalies involve changes in the set or structure of the chromosomes and are referred to as syndromes, such as Down syndrome or trisomy 21 is the best known, corresponding to the fourth most frequent cause of congenital anomalies. Chromosomal changes may be inherited or de novo originated, having biological influence or associated with environmental factors such as exposure to physical and chemical agents such as industrial wastes and agrochemicals. Diagnosis is made through karyotype analysis, and their knowledge is the basis for subsequent clinical treatment, prognosis, and risk-of-recurrence data for genetic counseling. Thus, the objective of this research was to analyze, through a retrospective study, human chromosomal disorders from regions of Brazil in the period of ten years (2005 to 2015), and correlates them with the use and occupation of soil through MaxEnt (maximum entropy) a predictive model for evaluation of association of occurrence of cases of chromosomal alterations as a function of soil use and occupation. In order to do so, a documentary study was carried out in the karyotype database of samples sent to the cytogenetic study of a national clinical laboratory. Of the 43,672 karyotype results, 83% (n= 36,435) were normal, 52% (n= 18,946) female and 48% (n= 17,489) male. Karyotypes with chromosomal abnormalities were found in 17% (n= 7,237), where 52% (n= 3763) female and 48% (n= 34740) male, were the most frequent aneuploidies (77% 5.558), structural changes totaled 16% (n = 1,163) and concomitant numerical and structural changes 7% (n= 516). 79.2% of the alterations involved autosomal chromosomes and 20.3% sex chromosomes, and 0.48% involved both autosomal and sexual. Among the altered cases, 9% (n= 668) were detected in mosaic. Characterizing chromosomal diseases by regions of Brazil, the highest proportion was in the South region, with 6 cases changed/100,000 inhabitants, followed by the Midwest and North regions, with 4 cases/100,000 inhabitants. The Northeast and Southeast regions presented the lowest proportions (3 cases changed/100,000 inhabitants and 2 altered cases/100,000 inhabitants respectively). When characterizing chromosomal diseases by regions of Brazil, it was possible to observe that in absolute numbers the highest frequencies occurred in the North and Northeast regions. Structural autosomal alterations were more frequent in the Southeast region, and numerical and structural concomitants were more frequent in the Northern region. Changes in mosaics were more frequent in the South, Northeast and Center-West regions, and those of single lineage were significantly more frequent in the Southeast region. Regarding land use and occupation, urbanized areas had a higher probability of occurrence of chromosomal diseases (50 to 90%), followed by areas using permanent crops (40 to 50%). This research demonstrates the prevalence of chromosomal diseases and their geographic distributions in Brazil being of great value, since studies of this genre are scarce in Brazil and, can serve as a tool to identify the incidence and recurrence risk of chromosomal diseases, enabling genetic counseling and information for the elaboration of public policies that improve the patients quality of life.